Long-term safety evaluation of bimatoprost ophthalmic solution 0.03%: a pooled analysis of six double-masked, randomized, active-controlled clinical trials - Wirta D (Dove Medical Press, 2011)
David Wirta1, Amanda M VanDenburgh2, Emily Weng3, Scott M Whitcup4, Sef Kurstjens5, Frederick C Beddingfield III4,61Private Practice, Newport Beach, CA, USA; 2Clinical Development, 3Biostatistics, 4Research and Development, 5Global Drug Development, Allergan, Inc, Irvine, CA, USA; 6Department of Medicine, Division of Dermatology, David Geffen School of Medicine, UCLA, Los Angeles, CA, USABackground: Bimatoprost ophthalmic solution 0.03% was approved in the US for reducing intraoccular pressure (IOP) based on two double-masked, active-controlled clinical trials. Four additional long-term studies (≥ 12months) were conducted; however, the aggregate safety profile of the six studies has not been reported.Methods: Adverse events (AEs) were pooled from six double-masked, active-controlled, long-term clinical trials in which subjects received bimatoprost 0.03% once daily (QD) or twice daily (BID) as an eyedrop. AE terms were converted to MedDRA (V.11.0) Preferred Terms and analyzed.Results: In total, 1409 patients received more than one dose of bimatoprost 0.03% QD or BID. Most AEs were mild in severity and reported by 86.7% (QD) and 94.8% (BID) of subjects (≤ 12 months of treatment). AEs reported through month 12 (aggregate incidence of ≥ 5%) were conjunctival hyperemia, increased eyelash growth, eye pruritus, periocular skin hyperpigmentation, eye irritation, dry eye, and hypertrichosis. AE onset was generally reported within four months of treatment. The cumulative incidence of common AEs in the QD treatment group at 24–48 months was similar to that measured at 12 months of treatment.Conclusion: Bimatoprost 0.03% has a favorable safety and tolerability profile as characterized by six long-term studies. Common AEs were due to the known pharmacological activity of bimatoprost and reversible with treatment cessation.Keywords: intraocular pressure, eyelids, pharmacology, clinical trial, medical treatment